2015
DOI: 10.1074/jbc.m114.616870
|View full text |Cite
|
Sign up to set email alerts
|

Interactions with the Bifunctional Interface of the Transcriptional Coactivator DCoH1 Are Kinetically Regulated

Abstract: Background:The protein dimerization cofactor of HNF-1 (DCoH1)/pterin-carbinolamine dehydratase (PCD) accomplishes two unrelated activities, forming two complexes with the same interface. Results: The DCoH1 homotetramer is kinetically trapped; a single mutation in the interface increases the unfolding rate 10 9 -fold. Conclusion: Kinetic regulation allows DCoH to assume two unrelated functions. Significance: Mutations excluding water from interfaces represent kinetic "hot spots," dramatically affecting dissocia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…The major difference in the recognition helices of PCBD1 and PCBD2 is located at residue 51 and 78, respectively. 28,29,40 However, mutating this "kinetic hotspot" did not modulate their transcriptional activity. In contrast, deleting the N-terminal sequence of PCBD2, that is missing in the PCBD1 sequence, did increase HNF1β promoter activity compared to the activity observed in presence of the normal functioning PCBD2.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…The major difference in the recognition helices of PCBD1 and PCBD2 is located at residue 51 and 78, respectively. 28,29,40 However, mutating this "kinetic hotspot" did not modulate their transcriptional activity. In contrast, deleting the N-terminal sequence of PCBD2, that is missing in the PCBD1 sequence, did increase HNF1β promoter activity compared to the activity observed in presence of the normal functioning PCBD2.…”
Section: Discussionmentioning
confidence: 91%
“…The KCNJ16 promoter activation was reduced (42%) in presence of PCBD2 while PCBD1 did not alter HNF1β function. The major difference in the recognition helices of PCBD1 and PCBD2 is located at residue 51 and 78, respectively 28,29,40 . However, mutating this “kinetic hotspot” did not modulate their transcriptional activity.…”
Section: Discussionmentioning
confidence: 98%
“…The pterin-4-alpha-carbinolamine dehydratase (PCD) functions both as a metabolic enzyme and as a transcriptional coactivator of transcription factor hepatocyte nuclear factor 1 ( Wang et al., 2015 ). Meanwhile, gephyrin can regulate the release of insulin.…”
Section: Discussionmentioning
confidence: 99%
“…The KEGG metabolic analysis of CpsD showed that the enzyme is part of pterin carbinolamine dehydratase subsystem in BtAOA and its role in the subsystem is PCD (EC 4.2.1.96). PCD plays a bifunctional (regulatory and catalytic) role in PheOHS (Naponelli et al 2008;Wang et al 2015) and is also involved in folate biosynthesis in bacterial system (Engevik et al 2019;Kok et al 2020).…”
Section: Recruitments Of These Genes Intomentioning
confidence: 99%